Evaluating Visitor’s Preferences of Ecotourism and Management Attributes in Kubah National Park: A Choice Experiment Approach - Nor Afiza, Abu Bakar; Dayang Affizzah, Awang Marikan; Salbiah, Edman; Siti Aisyah, Ya'kob (Universiti Kebangsaan Malaysia (UKM), 2018)
The growing numbers of national parks worldwide have somehow attracted the interests of nations around the world as it is now one of the important income generator for the tourism industry of a particular country. Since its inauguration, the concept of national parks has developed and expanded based on the important attributes of its environmental resources, albeit it is frequently affliated to the possibilities of conservation and preservation of the biodiversity and its environment. The central motivation for this study is to estimate visitor’s preferences for improvement in ecotourism and management in Kubah National Park (KNP) by utilizing the economic valuation tools, specifcally the choice experiment (CE) model. Accordingly, the focus of this study is limited to the valuation of ecotourism and management attributes of KNP, Sarawak, Malaysia. Choice experiment of the stated preference approach was utilized and fve attributes of ecotourism and management attributes were identifed, namely; (i) amenities (AMT), (ii) information availability (INFO), (iii) interpretive trails availability (ITA), (iv) park guide availability (PG) and (v) entrance fee charges (MPRICE). Information and statistics were gathered using questionnaires from face-to face interviews. Conditional logit (CLGT) model analyses involving a sample of 303 respondents was carried out.